2023
DOI: 10.3390/children10020252
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status and Circulating Levels of Fat-Soluble Vitamins in Cystic Fibrosis Patients: A Cohort Study and Evaluation of the Effect of CFTR Modulators

Abstract: Background: Improved therapy in CF has led to an overall improvement in nutritional status. The objectives of our study are: to cross-sectionally assess nutritional status and serum levels of fat-soluble vitamins; to retrospectively evaluate the efficacy of modulators on nutritional status and fat-soluble vitamin levels. Methods: In patients younger than 2 years of age, we evaluated growth, in patients aged 2–18 years, we assessed BMI z-scores, and in adults, we assessed absolute BMI values. Levels of 25(OH)D,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…There were no differences in levels of tocopherol and 25hydroxyvitamin D before and after ETI treatment. 41 In other studies examining the impact of ETI treatment on vitamin status, Wright et al 42 observed a modest increase in vitamin D levels in 76 adults after 1 year of treatment whereas Francalanci et al 43 showed significant increases in vitamin A, E and D levels in 29 adults who had been using modulators for at least 1 year. The mechanisms by which ETI affects vitamin levels remain poorly understood but may relate to improved absorption and metabolism of these vitamins combined with a decrease in the adherence to supplementation as patients start to feel better.…”
Section: Pancreatic Insufficiency and Nutritionmentioning
confidence: 99%
“…There were no differences in levels of tocopherol and 25hydroxyvitamin D before and after ETI treatment. 41 In other studies examining the impact of ETI treatment on vitamin status, Wright et al 42 observed a modest increase in vitamin D levels in 76 adults after 1 year of treatment whereas Francalanci et al 43 showed significant increases in vitamin A, E and D levels in 29 adults who had been using modulators for at least 1 year. The mechanisms by which ETI affects vitamin levels remain poorly understood but may relate to improved absorption and metabolism of these vitamins combined with a decrease in the adherence to supplementation as patients start to feel better.…”
Section: Pancreatic Insufficiency and Nutritionmentioning
confidence: 99%
“…It has been suggested that such improvements in the long term might lead to a reduction of osteopenia and fracture risk in adults with CF. Moreover, Fancalanci and collaborators reported in a recent study that ETI therapy not only increased BMI and vitamin D absorption but also vitamins A and E absorption in PwCF, demonstrating the ability of this therapy in improving nutritional status [ 107 ].…”
Section: Clinical Outcomes Of Eti Therapy In Case Reports Observation...mentioning
confidence: 99%
“…Parameters related to nutrient absorption such as weight, BMI, cholesterol and albumin were all significantly increased and the lipid profile improved independent of the diet composition ( Carnovale et al, 2022 ; Petersen et al, 2022 ). Serum levels of fat-soluble vitamins increased ( Wright et al, 2022 ; Francalanci et al, 2023 ) even leading to singular cases of hypervitaminosis ( Miller and Foroozan, 2022 ; Wisnieweski et al, 2022 ). These findings call for adjustments in vitamin supplementation.…”
Section: Intestine Pancreas Liver and Nutritionmentioning
confidence: 99%
“…Sweat chloride ppFEV1 Body weight increased (Wright et al, 2022;Francalanci et al, 2023) even leading to singular cases of hypervitaminosis (Miller and Foroozan, 2022;Wisnieweski et al, 2022). These findings call for adjustments in vitamin supplementation.…”
Section: Cftr Genotypementioning
confidence: 99%